ANALISIS KUALITAS AIR SEBAGAI DASAR PEMANFAATAN PADA LAHAN PERTANIAN DESA SABUHUR KABUPATEN TANAH LAUT - Elma Sofia; Ulfa Fitriati; Muhammad Afief Ma'ruf; Eddy Nashrullah; Muhammad Hafi (Jurnal Infrastruktur, 2026)
Agriculture is a crucial sector in Indonesia’s economic development. It provides food for the population, feed and energy resources, and serves as a primary source of livelihood for rural communities. To enhance rice production, one key government program is the development of irrigation networks. These networks play a vital role in agriculture and directly impact both the quality and quantity of rice yields. Regions with natural resources that are suitable for tidal or swamp irrigation systems are continually evaluated and developed. These areas are used for agriculture, aquaculture, and water transportation. This study analyzes water quality to determine its suitability for agricultural use as outlined in Government Regulation No. 22 of 2021. Parameters measured include field assessments of physical water quality using the U-50 HORIBA multi water quality checker. These parameters cover temperature, acidity, electrical conductivity, dissolved oxygen, and total dissolved solids. The research site is Sabuhur Village, Jorong District, Tanah Laut Regency, South Kalimantan Province. Measurements of physical and chemical water quality show that water conditions in agricultural land and nearby rivers or ponds are within acceptable ranges to support farming. This condition confirms that the surrounding aquatic environment does not pose significant constraints on plant growth and instead serves as a key factor in agricultural productivity. Thus, the water at the research site is suitable for agricultural use. However, further research is needed on soil characteristics, both physical and chemical.